Direct growth of plasmonic nanorod forests on paper substrates for low-cost flexible 3D SERS platforms. (20th January 2017) - Araújo, Andreia; Pimentel, Ana; Oliveira, Maria João; Mendes, Manuel J; Franco, Ricardo; Fortunato, Elvira; Águas, Hugo; Martins, Rodrigo
Abstract: Paper substrates, coated with ZnO nanorods (NRs) decorated with Ag nanoparticles (NPs), allowed the production of inexpensive, highly-performing and extremely reproducible three-dimensional (3D) SERS platforms. The ZnO NRs were synthesized by a simple, fast and low-temperature hydrothermal method assisted by microwave radiation and made SERS-active by decorating them with a dense array of silver nanoparticles deposited via a single-step thermal evaporation technique. Using Rhodamine 6G (R6G) as a probe molecule, with an amount down to 10 −9 M, the SERS substrates allowed a Raman signal enhancement of 10 7 . The contribution of the inter-Ag-NPs gaps for 3D geometry, ZnO NRs orientation and the large sensing area allowed by the NR scaffolds, were determinant factors for the significant Raman enhancement observed. The results demonstrate that plasmonic nanorod forests, covered with Ag NPs, are efficient SERS substrates with the advantages of being recyclable, flexible, lightweight, portable, biocompatible and extremely low-cost.